2016
DOI: 10.1007/s40262-016-0403-6
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Aspects of the Two Novel Oral Drugs Used for Metastatic Castration-Resistant Prostate Cancer: Abiraterone Acetate and Enzalutamide

Abstract: Two novel oral drugs that target androgen signaling have recently become available for the treatment of metastatic castration-resistant prostate cancer (mCRPC). Abiraterone acetate inhibits the synthesis of the natural ligands of the androgen receptor, whereas enzalutamide directly inhibits the androgen receptor by several mechanisms. Abiraterone acetate and enzalutamide appear to be equally effective for patients with mCRPC pre- and postchemotherapy. Rational decision making for either one of these drugs is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 23 publications
0
66
0
Order By: Relevance
“…A number of hypotheses have been proposed to explain the difference in cross‐resistance between these two agents. First, enzalutamide induces CYP3A4, an enzyme responsible for abiraterone metabolism; thus, abiraterone used after enzalutamide might be metabolized earlier. Indeed, a recent prospective study indicated a correlation between plasma trough levels of abiraterone and both PSA response and PFS .…”
Section: Discussionmentioning
confidence: 99%
“…A number of hypotheses have been proposed to explain the difference in cross‐resistance between these two agents. First, enzalutamide induces CYP3A4, an enzyme responsible for abiraterone metabolism; thus, abiraterone used after enzalutamide might be metabolized earlier. Indeed, a recent prospective study indicated a correlation between plasma trough levels of abiraterone and both PSA response and PFS .…”
Section: Discussionmentioning
confidence: 99%
“…The DDI profiles of abiraterone and enzalutamide have recently been described by Del Re et al . and are shown to be very different . Potential DDIs with abiraterone are likely to cause increased plasma levels of co‐administered drugs metabolized through CYP2D6 (risk of toxicity) which are ~20% of all drugs, while enzalutamide causes decreased plasma levels of co‐administered drugs (risk of subtherapy) metabolized through CYP3A4, CYP2C19 and CYP2C9, which are involved in the biotransformation of ~50% of all drugs .…”
Section: Discussionmentioning
confidence: 99%
“…Idelalisib (Ballantyne and Garnock-Jones, 2013), Crizotinib (Forde and Rudin, 2012), Fedratinib (Xu et al, 2014), Dasatinib (Haouala et al, 2011), Abiraterone (Benoist et al, 2016), Bicalutamide (Meulenbeld et al, 2013), Aprepitant (Majumdar et al, 2003), Imatinib (Majumdar et al, 2003) Increase the level of CQ CYP2D6 inducers --CYP2D6 inhibitors…”
Section: Ivermectinmentioning
confidence: 99%